Design and building of a room light control System based on iot arduino cloud - Sawidin, Sukandar Kandar; Patabo, Muchdar Dg.; Tuwongkesong, Samsu; Waroh, Anthoinete P.Y.; Kereh, Tracy M.; Lapon, Jeremia J. (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
The development of Internet of Things (IoT) technology opens up various opportunities to improve efficiency and convenience in various aspects of life, including in the management of electrical devices in the room. One of the innovative solutions that utilizes IoT technology is the Arduino Cloud-based room light control system using the NodeMCU ESP8266 microcontroller. This system is specifically designed to improve the efficiency of using room lights in the PLC laboratory of the Electrical Engineering department. This research aims to design and develop an Arduino Cloud-based IoT room light control system that can be controlled remotely using an Android device, PC, or laptop. NodeMCU ESP8266, as the core of this system, is a microcontroller that can connect with IoT, allowing users to control room lights via WiFi network. With this system, it is expected that users can control the PLC laboratory room lights in the Electrical Engineering department more easily, practically, and efficiently. In addition, this system is also expected to help save energy usage in the room. This research uses the method of designing and making a room light control system based on IoT Arduino Cloud. The research stages include system design, hardware and software development, and system testing. The test results show that the developed room light control system is able to turn on and off four lights in the PLC laboratory room via WiFi network using an Android device. In addition, this system is also equipped with an On/Off switch that can be used in the event of internet communication disruption. Thus, the IoT Arduino Cloud-based room light control system using the NodeMCU ESP8266 microcontroller is proven to provide convenience and efficiency for users in managing lighting in the PLC laboratory of the Electrical Engineering department, while helping to save energy.